STRATEGI GURU KELAS DALAM MENGATASI KESULITAN BELAJAR AKADEMIK SISWA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Riadatul Fardhani; Haifaturrahmah; Nursina Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe classroom teachers’ strategies in addressing students’ academic learning difficulties in elementary schools using a qualitative approach with a case study design. The findings indicate that teachers conduct early identification of learning barriers through observation, task analysis, and communication with parents. The strategies implemented include remedial teaching, the use of concrete and visual learning media, individualized assistance, and adaptive classroom management to enhance students’ comprehension and confidence. Continuous evaluation is carried out through formative tests, direct monitoring, and constructive feedback. Supporting factors include positive teacher-student relationships and a conducive learning environment, while the main challenges consist of students’ varying abilities, limited time, and insufficient learning facilities. Overall, the results emphasize that teachers play a crucial role in overcoming learning difficulties through well-planned, flexible, and responsive instructional strategies tailored to students’ needs.Kata Kunci: teacher strategies, learning difficulties, academic learning, elementary school, qualitative approach